Analysis of Tourism Management: Optimization of Resources and Asset Management of Gubuk Klakah Tourism Village - A. Muammar Alawi; Alfiandi Imam Mawardi; Wahyuni (Nusantara Science and Technology Proceedings, 2023)
Gubuk Klakah Village as one of the developing tourism villages in Malang Regency still has difficulties in managing and utilizing the BUMDes institution to optimize the increase of BUMDes PAD in Gubuk Klakah Village, namely a) human resource management that is still not optimal because the majority of BUMDes administrators are board members in other village tourism institutions so that there is overlapping in authority and division of tasks and b) there is still an unhealthy tourism organization culture such as distrust between members and financial smuggling for personal interests. Based on this background, the proposing team took three problem formulations, namely a) regarding the status quo of BUMDes management, b) the perception of the government and other institutional members towards BUMDes performance, and c) strategies to improve the performance of BUMDes Shack Klakah. The theories and concepts used in this research are change leadership, social perception theory, and asset-based community development. This research will be conducted in three stages, namely the preparation stage, the field study implementation stage, and the evaluation stage. The results of the discussion regarding Human Assets, Social Assets, Natural and Physical Assets, and Financial Assets, can be concluded that BUMDes Amanah Tourism Business Unit of Gubugklakah Village is reorganizing policies and bylaws. BUMDes Amanah Tourism Business Unit has optimized Natural and Physical Assets by packaging these assets into innovative and creative tour packages to attract tourist visits.